Влияние тиольных антиоксидантов на состояние нитрозирующего стресса в головном мозге крыс, подверженных хронической алкогольной интоксикации - Беленичев, И. Ф.; Кучер, Т. В.; Бєленічев, Ігор Федорович; Кучер, Тетяна Володимирівна; Belenichev, I. F.; Kucher, T. V. (My University, 2016)
Мета дослідження – вивчення впливу ацетилцистеїну, гептралу і тіоцетаму на показники нітрозуючого стресу в головном мозку щурів, яких піддавали хронічній алкогольній інтоксикації. Досліди проводили на білих безпородних щурах-самцях з масою тіла 180–220 г. Хронічну алкогольну інтоксикацію (ХАІ) викликали щоденним внутрішньошлунковим введенням перші 10 днів 15 % розчину етанолу в дозі 4 г/кг, наступні 10 днів – 15 % розчину етанолу в дозі 6 г/кг, і наступні 10 днів щурам вводили 25 % розчин етанолу в дозі 4 г/кг. З 30 доби припиняли алкоголізацію та проводили експериментальну терапію, продовжували спостереження протягом 14 діб. Досліджувані препарати вводили внутрішньошлунково за допомогою металевого зонда: гептрал –100 мг/кг, N-ацетилцистеїн – 100 мг/кг, пірацетам – 250 мг/кг, тіоцетам – 250 мг/кг. Контрольна і інтактна групи отримували фізіологічний розчин. The article focuses on the problem of search of new methods of nitrosating stress correction which occurs during chronic ethanol intoxication with thiol scavengers of NO. The conception is based on the fact that the main mechanisms of neuron injury in chronic alcohol intoxication are the disturbance of nitric oxide synthesis and initiation of nitrosating stress. Thiol antioxidants – heptral, N-acetylcysteine, and thiocetam were studied. The aim of research was to study the influence of heptral, N-acetylcysteine and thiocetam on the indices of nitrosating stress in the brain of rats exposed to chronic ethanol intoxication. The research was provided on outbred male rats with body mass 180–220 g. Chronic alcohol intoxication was caused by daily administration of ethanol into the stomach. For the first 10 days 15 % ethanol was given in the dose 4 g/kg, next 10 days 15 % ethanol was given in the dose 6 g/kg, the last 10 days 25 % ethanol was given in the dose 4 g/kg. After that alcoholisation was ended and experimental therapy with the named drugs started. The observation of animals was held for the next 14 days. The drugs were administered into the stomach with the help of metallic tube in the following doses: heptral – 100 mg/kg, N-acetylcysteine – 100 mg/kg, pyracetam – 250 mg/kg, thiocetam – 250 mg/kg. The control and intact groups of animal were given saline solution. The results of study demonstrate that experimental modeling of chronic alcohol intoxication led to activation of nitrosating stress in the experimental rats brain. The increase of NOS activity, content of stable NO metabolites and nitrotyrosine evidenced about it.
Вплив тіольних антиоксидантів на стан нітрозуючого стресу в головному мозку щурів, яких піддавали хронічній алкогольній інтоксикації
The influence of thiol antioxidants on the state of nitrosating stress in brain of rats with chronic ethanol intoxication
Keywords: хронічна алкогольна інтоксикація; нітрозуючий стрес; N-ацетилцистеїн; гептрал; тіоцетам; chronic ethanol intoxication; nitrosating stress; N-acetylcysteine; heptral; thiocetam